Achieving Market Superiority: An Innovative Approach to Marketing and Sales Strategy in the Bitumen Industry (Case Study: Bitumen Industry) - Esfandiar, Masoud; Asayesh, Farzad; Rousta, Alireza; Hashemi, Seyed Mahmood (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The objective of this study was to develop a marketing and sales model for industrial markets.Methodology: This research is applied in nature and follows a qualitative approach based on grounded theory. Methodological triangulation was employed in this study, using various data collection methods such as literature review, examination of specialized sources and texts, as well as semi-structured interviews. A purposive sampling technique was used to interview 14 managers and experts from companies active in the bitumen industry in the year 2024. The interviews were coded using ATLAS.TI software. To validate the findings, data were evaluated and analyzed for reliability based on triangulation.Findings: Based on the grounded theory model designed for marketing and sales in industrial markets, four causal conditions (product quality, pricing, production capabilities, and product innovation), five contextual conditions (economic conditions, regulations, political conditions, technology, and market conditions), four intervening conditions (international relations, cultural factors, climate change, and unexpected events), four strategies (financial strategies, brand management, customer analysis, and product quality improvement), and five outcomes (increased market share, increased customer satisfaction, increased profitability, market differentiation, and optimized marketing performance) were identified.Conclusion: The marketing and sales model in industrial markets, especially in the bitumen industry, requires specific approaches that differ significantly from other industries. In this industry, emphasis on long-term relationships with customers, extensive networking, and strong connections with key customers is of utmost importance. Companies should focus on establishing strategic relationships with major customers, such as construction contractors and road construction companies, to leverage the long-term benefits of these relationships.